DEEP LEARNING BASED PREDICTION MODEL FOR COURSE REGISTRATION SYSTEM - T.M.Nithya, K.S.Guruprakash, L.Amudha (International Journal of Advanced Science and Technology, 2020)
Nowadays in any educational system, selecting course by students according to their need is achallenging task. This paper proposed deep learning approach to predict the courses for the studentaccording to their cutoff marks. The cutoff mark of student is calculated for this course prediction whichanalyzes the accurate course to choose for their college education. Choosing the appropriate course inany educational institution with infrastructure facilities is the major drawback in the existing system. Theexisting system will only give the information about the institutions. To overcome the anomalies of theexisting system this system proposes the effective course registration system using deep learning basedprediction model. The major technique used to predict the course is Decision Tree Algorithm. Thisalgorithm comes under the Deep Learning Technique which comes under Artificial Intelligences that willprocess the cutoff mark of the student to know about the Science and engineering colleges. This algorithmwill analyze the uploaded dataset of the various courses in the colleges and the facility that are providing.The student will initially register their details before logging in to the website. This application will filterthe data based on cutoff mark when the student login to the homepage. This will sort out the courseinformation on basis of their cutoff marks. The advantage of the proposed system is that the student canchoose the course that they need to study with the accurate predicted data. The Arts and EngineeringCollege are uploading the detail in admin. The BE course are CS, ECE AND EEE are available in courseprediction